The effect of community mobility changes to air quality in Java-Bali during the early phase of COVID-19 pandemic - Hening Tyas Subekti; Joko Christanto (Sustinere: Journal of Environment and Sustainability, 2022)
Previous studies found a reduction in pollution levels when travel was banned due to the COVID-19 pandemic. This study aims to identify the changes in community mobility and air quality, as well as to analyze the effect of community mobility changes on air quality during the early phase of the COVID-19 pandemic. This study used daily secondary data from Google Mobility Report and station data archive of Air Quality Monitoring System (AQMS) which records Air Pollutant Index Standard (ISPU). This study focused on the early phase of the pandemic (15th Feb – 15th June 2020) in six provinces in Java and Bali. This study used panel regression and GIS. The results show that there is 35-90% reduction in mobility and also some decreases in air quality pollutants. Furthermore, it was shown that there is a positive relationship between ISPU and mobility. Community mobility explains ISPU in Bali, the Special Region of Yogyakarta, the Special Capital Region of Jakarta, West Java, Central Java, and East Java by 24%, 53%, 13%, 3.7%, 20%, and 39% respectively. Meanwhile, the combined influence of the six provinces is 18.8%. The variable that has a significant effect is the community mobility changes on transit stations. Every 1% increase in the transit station's mobility is capable to increase ISPU by 0.4.